Study of acrosome formation, interspecific and intraspecific, in the testicular lobes of some pentatomid species - Souza, Hederson V. [UNESP] (2010)
The objective was to compare the formation of the acrosome in the testicular lobes of the species Antiteuchus tripterus F. and Platycarenus umbractulatus F., belonging to the subfamily Discocephalinae, and Euschistus heros F., Mormidea quinqueluteum L., Oebalus sp. and Thyanta perditor F., belonging to the Pentatominae (Heteroptera: Pentatomidae). It was found that, in general, the behavior of periodic acid Schiff-positive granules for all of the species analyzed is similar for these species. In the beginning of spermiogenesis, there is a central granule that migrates to one of the extremities of the spermatid, and later, it becomes elongated and cannot be distinguished in the spermatozoa. Some species such as A. tripterus, E. heros and P. umbractulatus showed significant differences in the behavior of the PAS-positive granule in certain lobes, suggesting the formation of spermatozoa with non-fertile functions.